Process redesign as a key strategy for service innovation: a case in a consulting company - Érica Melo Araújo (2020)
Research in the scope of service innovation through the analysis and subsequent redesign of a key process of an internationalization consulting company, in order to offer services with greater added value, meeting the needs of customers and increasing the company's internal operational efficiency.